Iatrogenic aortic dissection after minimally invasive aortic valve replacement: a case report. Issue 1 (December 2016) - Ramadan, Mohamed; Buohliqah, Lamia; Crestanello, Juan; Ralston, James; Igoe, David; Awad, Hamdy
Abstract Background As minimally invasive cardiac and vascular procedures are on the rise, the incidence of iatrogenic acute aortic dissection (IAAD) will increase. Cardiovascular professionals should be aware about the risk factors, means of prevention and best management options for IAAD in the perioperative setting. Case presentation We present the successful clinical management of a complicated case of IAAD after minimally invasive aortic valve replacement. Conclusion High index of suspicion is required for prompt diagnosis of IAAD; collaboration of the whole perioperative team is imperative for management of this catastrophe.